Guest

If z + 3 = 5, then z = . If z + 3 = 5, then z = . If z + 3 = 5, then z = .

 If z + 3 = 5, then z =                                .
 If z + 3 = 5, then z =                                .
 If z + 3 = 5, then z =                                .

Grade:12

1 Answers

Harshit Singh
askIITians Faculty 5964 Points
one year ago
Dear Student

Consider the equation, z + 3 = 5
Transpose 3 to RHS it becomes -3
z= 5–3
z =2

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free